Network Structure as a Determinant of Foreign Direct Investment Based Competitive Advantage - Buyukbalci, Pinar (OECONOMICA PUBLISHING HOUSE, 2017)
Management of the international value chain requires managers to better understand the impact of ties in company's operational network. Apart from the structural side of the network, the relational side also emerges as a critical perspective to fully understand the mechanisms affecting the investment success of MNEs in certain contexts. In parallel with these, the conceptual framework and research proposals presented in this study aim to cover these main aspects, while attempting to explain the impact of network relations on the investment patters of MNEs. Specifically the relation between foreign direct investment patterns of MNEs in terms of value chain structure and generic strategies of cost and differentiation is the backbone of the model proposed here. The study further attempts to clarify this relationship by putting it into a framework consisting of moderating variables consisting of relational embeddedness determinants and networking behaviour mode.
Keywords: Foreign Direct Investment; Cost Leadership; Differentiation; Value Chain; Network Ties; Network Structure; STRATEGIES; Business & Economics; International Relations